CHALLENGES AFFECTING TEACHERS’ COMPETENCY IN IMPLEMENTING THE 21ST-CENTURY CURRICULUM IN SECONDARY SCHOOLS IN SOUTH-WEST NIGERIA - Aina, Gbenga (Global Synthesis in Education Journal, 2025)
This study aimed to explore the challenges impacting teachers' competency in implementing the 21st-century curriculum in secondary schools across South-West Nigeria. A descriptive cross-sectional survey design was utilized, with the target population consisting of secondary school teachers from the six South-West states: Ondo, Oyo, Osun, Ekiti, Lagos, and Ogun. A total of 860 teachers were selected using a multistage sampling technique to ensure representation. Data were collected through a 15-item questionnaire developed by the researcher, titled "Teachers' Competency for the Implementation of the 21st-Century Curriculum among Secondary Schools in South-West Nigeria." The questionnaire was validated for content and face validity by measurement and evaluation experts at Ekiti State University. Reliability was assessed using the test-retest method, with a reliability coefficient calculated using Pearson's Product Moment Correlation Coefficient (PPMCC) at the 0.05 significance level. The questionnaire was distributed to teachers in their respective schools with support from research assistants. Data analysis included percentages, frequency counts, and mean scores for research questions, with an independent t-test employed to test hypotheses at the 0.05 level. Key findings indicated that significant barriers to teacher competency included inadequate human and material resources, insufficient commitment, a lack of mastery of the curriculum, limited government support and funding, poor supervision, and inadequate time to manage heavy workloads. The study recommends increased government funding, enhanced teacher training programs, improved supervision systems, and better resource allocation to boost teacher competency in applying the 21st-century curriculum